ANALYSIS OF THE MUSICAL FORM OF KEDU’E AS AN ACCOMPANIMENT OF EAST SABU ETHNIC PADOA DANCE AT IE LOWE WINI STUDIO, AIR NONA VILLAGE, KOTA RAJA DISTRICT, KUPANG. - FLORA CEUNFIN; MARIA KLARA AMARILIS CITRA SINTA DEWI TUKAN (LPPMPP Institut Seni Indonesia Padangpanjang, 2020)
Pedoa dance is one of the traditional dance of East Nusa Tenggara, precisely from the Eastern Sabu Region. Pedoa dance in its presentation uses song and Kedu’e as accompaniment. Kedue is a rhythmic musical instrument that is tied to the feet of Pedoa dancers. The problem is how the musical form of Kedu'e as an accompaniment to the East Sabu ethnic Pedoa dance at the Ie Lowe Wini studio, Air Nona Subdistrict, Kota Raja District, Kupang City. The uniqueness that is found in the Pedoa dance is the presence of the Kedu'e musical instrument that is tied to the dancer's feet. Thus there are eight (8) Kedu'e rhythm patterns or Pedoa dance rhythm patterns, namely (1) Tede rhythm patterns or Tede Motion Variations, (2) Manale rhythm patterns or Manale movements, (3) Hala rhythm patterns Hala motions, (4) Heroda Rhythm Patterns or Heroda range of motives, (5) Dede Rhythm Patterns or Dede Motion patterns, (6) Lung Rhythm Patterns or Lung motion variations, (7) Hegede Rhythm Patterns or Hegede Motion Variations, (8) The My Rhythm Pattern or My Variety of My Motion. The above rhythmic patterns vary in tempo, namely Andante, Moderato and Allergo. The tempo variation follows the rhythm of the song that is sung by dancers while dancing Pedoa, besides that the tempo change especially from Andante ketempo Alergo is a consideration so that dancers can take power in a variety of fast tempo dance moves. The rhythm or tempo produced by these two musical instruments will give enthusiasm to dancers and add an Estonian and dynamic feeling to the Pedoa dance.